Overcoming discourse-linking difficulties in aphasia: The case of clitic pronouns (2020)
The present study aims to contribute to the ongoing discussion about the impact of discourse-linking deficits on the performance of individuals with aphasia by providing new data from a set of rarely investigated constructions: sentences in which a clitic pronoun coexists alongside with the full DP it agrees with. To do so, we use data of individuals with non-fluent aphasias who need to overcome the difficulties in direct object (accusative) clitic production. This results in overproduction of non-target clitic right dislocations (RDs) and clitic doubling (CD). Data from 15 individual’s native speakers of Spanish and Catalan are discussed. Data complement the results of previous investigations on discourse-linking effects in these languages, allowing the interpretation of results across constructions.